Improving the thermal insulation and mechanical properties of concrete using Nano-SiO2 - Alaa N. Saleh (Elsevier, 2021)
The use of nanotechnology in the construction industry and building structures is one of the important topics of construction engineering today. This study aims to discover the effect of Nano-silica (SiO2) on concrete's mechanical and thermal properties, such as thermal conductivity, specific heat capacity, thermal diffusivity, and compressive strength. It is studied and discussed in this article. Nano-silica was added at percentages (1%, 2%, and 3%) as a replacement percentage of the weight of the cement. It was noted through the results that there is a decrease in the thermal conductivity coefficient values, which ranged between (0.5–0.92) W/m °C in the mixtures containing Nano-silica, which means an increase in the thermal insulation ability of Nano-concrete by (41.8%, 53.15%, and 65.57%) respectively. A decrease in the specific heat capacity values was observed compared to conventional concrete. The values of the specific heat capacity of Nano-concrete increased to 896 when J/kg K for 3% Nano silica was added. Also, the results showed an increase in the compressive strength values of the models at rates of (21.49%, 24.25%, 32.45%) respectively, compared to the conventional concrete. We note that the maximum values of the compressive strength and the lowest value of the thermal conductivity coefficient were at a rate of (3%). It also became clear that the compressive strength also increases with age. Finally, Thermal insulation of buildings is the most effective way to save energy in buildings, and the importance of the current article stems from obtaining concrete with good mechanical properties and distinctive thermal insulation.